Revisiting the paleolithic reindeer of Moldova: an in-depth analysis - Croitor, Roman (Acta et Commentationes Exact and Natural Sciences, 2023)
This study examines reindeer remains from Paleolithic sites in Moldova, including re-description and reclassification of antler findings, and identifies a previously undocumented complete antler from Cosăuți. The antler from Duruitoarea Veche is determined to be from red deer (Cervus elaphus), consistent with the site’s fauna. Using a t-test on talus samples, the study investigates body size variations between an older reindeer form from Duruitoarea Veche and Brînzeni 1, and the younger R. tarandus constantini from Cosăuți. Results show no statistically significant differences in body size, but confirm the larger cheek teeth in R. tarandus constantini. Reindeer from Rașcov 7 are reclassified as R. tarandus cf. constantini, with relatively large cheek teeth.